Retainer Agreement, July 29, 1983 - Houseal, Willie H. (Valdosta State University Archives and Special Collections, 1983)
The Retainer Agreement, dated July 29, 1983, is written by Willie Houseal as the Executive Director of the Winnerville's Coalition Consultants. The documents describes how Christopher Coates is seeking a Civil Action lawsuit against the City of Valdosta for present voting systems as unconstitutional and violating the Voting Rights Act of 1965, and describes the cooperation of the Winnersville Coalition Consultants for the suit..
1 electronic document, PDF, 2 scanned images
Keywords: Valdosta (Ga.); Lowndes County (Ga.); Correspondence; Voting Rights Act of 1965 (United States); Class actions (Civil procedure)